2021
DOI: 10.1159/000520894
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Expression of SGLT-2, GLUT1, and GLUT3 in Peritoneal Dialysis Patients

Abstract: Introduction: In peritoneal dialysis (PD) patients, the peritoneal membrane is affected by glucose-based solutions used as peritoneal dialysate fluids. This exposure leads to changes of the membrane which may eventually culminate in fibrosis and method failure. In vitro or animal studies demonstrated that glucose transporters are upregulated upon exposure to these solutions. Expression studies of glucose transporters in human peritoneum have not been reported yet. Methods: Expression of SGLT-2, GLUT1, and GLUT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…Peritoneal biopsy lysates were prepared as previously described [ 28 ]. TRX activity of 20 µg protein samples was analyzed using the fluorescence-based assay kit (FkTRX-04, BIOZOL, Eching, Germany) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peritoneal biopsy lysates were prepared as previously described [ 28 ]. TRX activity of 20 µg protein samples was analyzed using the fluorescence-based assay kit (FkTRX-04, BIOZOL, Eching, Germany) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Peritoneal biopsies were formalin-fixed in 4% buffered formalin and paraffin-embedded following routine protocols [ 29 ]. Immunohistochemistry was performed as previously described [ 28 , 30 , 31 ]. Used antibodies: anti-TXNIP (ab188865; 1:200, Abcam, Cambridge, UK), anti-TRX (sc-271281; 1:100, Santa Cruz), anti- γH2AX (9718S; 1:100, CST).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors therefore conclude that SGLT-2 inhibitors may have potential therapeutic benefit among PD patients. These drugs may reduce glucose absorption through the peritoneal membrane and delay the long-term deleterious effects of glucose on the transport function of the peritoneal membrane, thus prolonging its use and perhaps preventing EPS [ 44 ].…”
Section: Molecular and Genetic Studiesmentioning
confidence: 99%
“…There have been a limited number of studies exploring GLUT expression in the peritoneum. Studies in human peritoneal mesothelial cells have demonstrated expression of GLUT1, GLUT3, SGLT1, and even SGLT2, although results have been inconsistent among studies 4 6 . Exposure to high-glucose solutions in cell culture and animal models has also been demonstrated to upregulate GLUT expression, but again, results have varied across studies 4 …”
mentioning
confidence: 99%